PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Semarang Roru Cake) - Windi Nova Dayanti, 15.05.51.0015; Prabowo, Rokh Eddy (Students' Journal of Economic and Management, 2019)
The purpose of this study was to analyze the effect of each independent variable on price, service quality, and location perceptions of Semarang Roru Cake product purchasing decisions. The population in this study were all Semarang Roru Cake product buyers in the Semarang Regency region with a sample of 96 people. Research data is processed using the help of SPSS version 19. The results of data processing indicate that all indicators are valid and all variables are reliable. Variable perceptions of price, service quality, and location significantly influence the purchasing decisions of Semarang Roru Cake products.